GENDER DIVERSITY DAN KINERJA ESG : PERAN MODERASI GENDER EQUALITY PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Nurbaity, Cahya; Zarefar, Arumge; Rasuli, M (Universitas Riau, 2025)
Environmental, Social, and Governance (ESG) issues have gained global prominence as indicators of corporate sustainability and social responsibility. Growing pressure from investors, regulators, and the public has intensified demands for transparency, accountability, and awareness of the social and environmental impacts of business activities. This study examines the effect of gender diversity on ESG performance and investigates the moderating role of gender equality in this relationship. Using regression analysis with Stata, the study analyzes 356 observations from 197 non-financial companies. The findings reveal that gender diversity does not affect ESG performance, suggesting the presence of tokenism, where the limited number of women in organizational structures results in symbolic representation rather than substantive influence in decision-making. However, gender equality significantly strengthens the relationship between gender diversity and ESG performance. To the best of the researcher’s knowledge, this is the first study in Indonesia to explore gender equality as a moderating factor in the non-financial corporate sector. Theoretically, the study contributes to a deeper understanding of Resource Dependence Theory and Contingency Theory within the sustainability and corporate governance context of developing countries. Practically, the results highlight the need for regulators and policymakers to design regulations that promote gender equality at the top management level as part of national efforts to enhance ESG performance.